Professor Thomaz Galhardo: produção, circulação e práticas de alfabetização e leitura séculos XIX e XX - Alcanfor, Lucilene Rezende (2016)
This study investigates the historiographical production and circulation of Thomaz Galhardo s (1852-1904) school books, as well as literacy instruction and reading practices proposed by him. He was a primary education teacher who made from his production a political action in the public education scene of Sao Paulo state, during the end of the Empire and the first decades of Republic. As an intellectual, he held a privileged social position in strategic roles on public education and took part on the foundation of the first teacher associations of that state. He was actively involved on the organization of boards of education, and bills for the education amendment on this state. The study focused, however, on his activities as a school book author for primary education. Thomaz Galhardo was part of a new generation of didactic books authors, that from primary education started to produce a graduated series of reading books. He was known for this type of didactic material, especially as the author of Cartilha da Infância, a book which is part of the series Na escola e no Lar. Based on theoretical and methodological framework of Alain Choppin, this study intends to create an inventory of the production and circulation of this author, with particular attention to the peculiarities of the market for school books on that period. The analysis of the method proposed by Thomaz Galhardo allows us to place his works within the discussion of literacy and reading practices of the end of XIX century to the beginning of XX century, analyzing his production from the permanence of successive editions. This evidence proves the importance of school tradition, since the books used for literacy and reading, through their production and extent of use, have left deep marks on the thoughts concerning the knowledge of primary education on historical formation of literate societies